Analisa Kualitas Pelayanan Customer Service Terhadap Kepuasan Nasabah pada Bank China Construction bank Indonesia TBK - Sumardi Sumardi; Yeyen Anggraini (Lembaga Pengembangan Kinerja Dosen, 2022)
This journal aims to examine the effect of the variable quality of customer service on customer satisfaction. The research was conducted at the bank CCB KK LAGUNA PLUIT. Collection of this analysis by providing questionnaires to customers who come 150 samples. In this analysis, the service performed by Bank CCBI Laguna Pluit is to provide services by paying attention to accuracy, speed, friendliness, and speeding up queues so that they do not stagnate. Some of the customer service priorities are providing ATM machines that work with the Prima network with excess withdrawals and balance checks on the Prima network without being charged. Settlement of customer complaints quickly and precisely which in the end obtains very satisfying results by paying attention to CCBI bank services can maintain its customers until now. Companies must always improve and improve the quality of customer service provided so that customers who become will feel satisfied so that they will loyally use the products and services offered. This will have a positive impact in the future for the company.